Pengaruh Motivasi dan Pengalaman Kerja Terhadap Kinerja Pegawai Honor Dinas Perhubungan Kota Sungai Penuh - Poni Yanita (Jurnal Indonesia Sosial Teknologi, 2022)
Human resource management can be interpreted as a movement that recognizes the importance of people in government when with proper management, planning and development will be able to provide maximum contribution to an organization. The purpose of this research is to determine the effect of motivation and work experience on employee performance. Data analysis used descriptive and inferential methods. The sample measurement uses the Slovin formula with 92 respondents, namely full river city transportation service employees. The method used is descriptive causal quantitative in order to determine the causal relationship between research variables. The results of the study are that motivation does not have a high enough influence on employee performance because the value of t count < t table. However, work experience has a high enough influence on the quality of the performance of honorary employees with a value of t count > t table. In the F test, it is known that F arithmetic > F table, motivation and work experience can have a significant influence on employee performance with a large percentage of 20.2%, which means the other 79.8% are influenced by other factors.